CARING FOR THE EARTH AND HEALING STUDENTS THROUGH THE SYNERGY OF ISLAMIC ECOTHEOLOGY AND COUNSELING IN WASTE EDUCATION - Yulia Khairina Ashar; Fatma Indriani; M. Iqbal; Putri Safira; Agil Maritho Lauchan (Pusat Studi Gender dan Anak, 2025)
The issue of waste is a very pressing matter that requires serious attention because it has a direct impact on the environment, health, and the sustainability of human life. This study aims to increase the knowledge and attitudes of Islamic boarding school students. The objective of the study is to improve knowledge and attitudes to care for and heal Islamic boarding school students through the synergy of Islamic ecotheology and counseling in waste education. The type of research used in this study is quasi-experimental research with a one-group pretest-posttest design. This study involved 30 santri who were selected purposively based on recommendations from the pesantren. The statistical test used was the Paired Sample t-Test with the help of JASP version 16 computer software. The results of this study show that interventions in the form of counseling can significantly improve the knowledge and attitudes of santri regarding Islamic ecotheology and waste management in pesantren. The Wilcoxon test results showed a significant increase in knowledge (p < 0.001), while the Paired Sample t-Test showed an increase in attitude from an average score of 26.60 on the pretest to 36.10 on the posttest with a p-value < 0.001. This confirms that counseling not only improves conceptual understanding but also encourages positive attitude changes that have the potential to continue in real behavior in maintaining the cleanliness and sustainability of the pesantren environment.